Structural and functional alterations in hematological parameters among individuals at clinically high risk for acute lymphocytic leukemia - Mohd Afzal; Abhishek Sharma; Ashok Kumar Sah; Aksh Chahal (Iraqi Journal of Hematology)
Acute lymphocytic leukemia (ALL) is a diverse category of hematological malignancies defined by the clonal proliferation of immature lymphoid cells. While advances in diagnostic procedures and treatment modalities have improved results for many patients, a group of them exhibit clinical characteristics that indicate a high risk of disease progression and unfavorable consequences. Understanding the underlying molecular processes and developing accurate prognostic indicators in this high-risk group is critical for personalized treatment approaches and better patient outcomes. Hematological markers, immunophenotyping profiles, and chromosomal defects in people who were clinically high risk (CHR) for ALL are discussed in this review. Alterations in hematological markers, such as elevated white blood cell counts, decreased hemoglobin levels, and thrombocytopenia, are indicative of the aggressive nature of high-risk ALL. Immunophenotyping investigations revealed abnormal expression patterns of lineage-specific markers, indicating clonal proliferation and differentiation arrest. Furthermore, cytogenetic examination revealed frequent chromosomal defects, such as the Philadelphia chromosome and hyperdiploidy, which have been linked to a poor prognosis in ALL patients. The combination of hematological, immunophenotypic, and cytogenetic data gives a thorough knowledge of disease biology and assists in risk assessment for patients with CHR for ALL. The present review elucidates the intricate interaction of hematological, immunophenotypic, and cytogenetic abnormalities in persons at clinically high risk for ALL, emphasizing the importance of integrated diagnostic techniques to enhance patient outcomes and optimize treatment strategies.